Level of Self-confidence and Its Relationship to the Motivation of Performance among Team Sports Players at the Palestinian Universities - Thabet Shtewy (Sultan Qaboos University, 2017)
The study aimed at investigating the level of self-confidence and its relationship to motivation of performance among team sports players in Palestinian universities. Differences in the level of self confidence and motivation of performance according to university and type of game were detected. A purposive sample consisted of 90 players. A questionnaire was used as a tool to collect data. The results of the study showed that the level for both self-confidence and motivation of performance were high among league players in Palestine. There was a statistically significant positive correlation between self-confidence and motivation (r = 0.65). The results revealed that there were statistically significant differences in the level of self- confidence due to university and type of game. Also, there was a difference in the motivation between universities.